Manggo Frenzy - Mohamad, Muhammad Harith; Noor Bazlan, Nurhanisah Liyana; Mahmud, Muhammad Fauzi; Ridwan, Iskandar Zulfikar; Abdul Rahim, Mira Raimi; Mohd Khair, Nurul Izzati (2015)
Manggo Frenzy is a service business located at Plaza Angsana, No. 52, Jalan Tampoi, 81200 Johor Bahru, Johor. The store specializes in serving ice blended beverages, particularly targeting the entire family and those who enjoy the local fruit, mango. Manggo Frenzy serves walk-in customers and is committed to delivering the greatest taste of beverages made with high-quality ingredients.